Case Report: Usefulness, effectiveness, and safety of an advanced hybrid closed-loop system in a child with early identification of type 1 diabetes - Mameli, Chiara; Macedoni, Maddalena; Redaelli, Francesca; Petitti, Agnese; Hajro, Adelina; Bosetti, Alessandra; Zuccotti, Gianvincenzo (Frontiers in Endocrinology, 2025)
The usefulness, effectiveness, and safety of advanced hybrid closed-loop systems (AHCLs) in early-stage 3 type 1 diabetes (T1D) are unknown. We report 9 months of continuous glucose monitoring (CGM) outcomes in a patient with early-stage 3 T1D treated with the Tandem t:slim Control-IQ® system. A 13-year-old girl, affected by celiac disease and Hashimoto’s thyroiditis, was diagnosed with T1D without symptoms (fasting c-peptide: 1.77 ng/ml; HbA1c: 6.4%) following an outpatient T1D screening program. She wore a CGM at diagnosis to closely monitor her glucose profile. After 6 months, when the time in range (TIR) fell below 80%, the Tandem t:slim Control-IQ® was initiated. Standardized CGM metrics, as well as instances of severe hypoglycemia and diabetic ketoacidosis (DKA), were recorded. CGM data guided the initiation of early insulin therapy. Tandem t:slim Control-IQ® system proved effective from the onset of T1D, with a low insulin requirement (0.1 U/kg/day, < 10 units/day) and maintained good metabolic control (TIR > 80%) without severe hypoglycemia or DKA. Based on our experience, we suggest a two-step approach for monitoring and treating patients with early stage 3 type 1 diabetes: first, positioning CGM, and second, when TIR falls below 80%, considering the addition of an AHCLs, even if the patient has a low insulin requirement.